Sustainable consumption and production for Asia: sustainability through green design and practice - Tseng, Ming-Lang; Chiu, (Anthony) Shun Fung; Tan, Raymond R.; Siriban-Manalang, Anna Bella (Journal of cleaner production, 2013)
This special issue of the Journal of Cleaner Production addresses sustainability through green supply chain management, design and practice in Asia by examining opportunities for sustainable consumption and production (SCP). The articles present and analyze ‘top-down’ green efforts by policy makers and ‘bottom-up’ efforts by companies in the supply chain. The articles also showcase discussions on green supply practices, implications of lean production, green innovation, green supply chain management boundaries, and methods of assessing evaluation and implementation processes. Issues of sustainability are explored in different ways and in several contexts. Within the context of the environmental, social, and economic impacts of present and anticipated impacts on climate change, societal efforts toward sustainable consumption and production within a low-fossil carbon energy system are addressed and applied. This special issue identifies highlights factors such as advanced green technology, green consumerism, green innovations, appropriate sustainable business models, green and lean supply chain management as major concerns and key ingredients in promoting large-scale sustainable consumption and production.